Characteristics of the demographic system in the Romanian rural area: Developments at the regional level in the post-accession period and perspectives - Sorinel Ionel Bucur (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
Over the time, demography has been the subject of multiple researches, given its importance in the development process of any community. The population and the changes in its structure, as well as aspects related to birth, mortality or specific demographic indicators (economic dependency rate and demographic ageing index), represent the starting point in the development of any sustainable development strategy. In this context, the present approach aims to carry out an analysis of the demographic system in the Romanian rural area in the post-accession period, using data and public information from the national statistics, as well as information from relevant reports, with presenting of the main structural changes and existing gaps in regional level.
Keywords: J11; J12; J13; J14; 330; demography; structural changes; inter-regional gaps